The Impact Of Non-Shari’ah Compliant Income Of Islamic Banks In Pakistan: Trust As A Mediator To Commitment Of Customers - Usman, Muhammad (2021)
Islamic banking is a contemporary concept in the modern world, finding many solutions to the problems of the modern economic system. Shari’ah law is the backbone of this system which the philosophy of the system is derived from the Quran and the Sunnah of Prophet Muhammad SAW. Islamic banks (IBs) offer Shari'ah-compliant products to Muslims which is an essential element to gain acceptance among Muslims and maintain the confidence of all stakeholders and the general public especially related to Halal products. Also, there are certain factors (ability, benevolence, integrity, and shared values) that are essential to gain the trust and commitment of the customers in Islamic banking. Besides, non-Shariah income derived from non-Shariah compliant transactions is also a problem. Unlike conventional banks, this distinctive feature occurs within Islamic banking environments due to non-conformance with Shariah (Islamic law). For instance, USD 2421667.26 non-Shariah compliant income was reported in IBs' annual reports from 2013 to 2018.